The mesoeconomics of abortion: A scoping review and analysis of the economic effects of abortion on health systems. - Samantha R Lattof; Ernestina Coast; Yana van der Meulen Rodgers; Brittany Moore; Cheri Poss (PLoS ONE)
Background Despite the high incidence of abortion around the globe, we lack synthesis of the known economic consequences of abortion care and abortion policies at the mesoeconomic level (i.e. health systems and communities). This scoping review examines the mesoeconomic costs, benefits, impacts, and values of abortion care and policies. Methods and findings Searches were conducted in eight electronic databases. We conducted the searches and application of inclusion/exclusion criteria using the PRISMA extension for Scoping Reviews. For inclusion, studies must have examined at least one of the following outcomes: costs, benefits, impacts, and value of abortion care or abortion policies. Quantitative and qualitative data were extracted for descriptive statistics and thematic analysis. Of the 150 included mesoeconomic studies, costs to health systems are the most frequently reported mesoeconomic outcome (n = 116), followed by impacts (n = 40), benefits (n = 17), and values (n = 11). Within health facilities and health systems, the costs of providing abortion services vary greatly, particularly given the range with which researchers identify and cost services. Financial savings can be realized while maintaining or even improving quality of abortion services. Adapting to changing laws and policies is costly for health facilities. American policies on abortion economically impact health systems and facilities both domestically and abroad. Providing post-abortion care requires a disproportionate amount of health facility resources. Conclusions The evidence base has consolidated around abortion costs to health systems and health facilities in high-income countries more than in low- or middle-income countries. Little is known about the economic impacts of abortion on communities or the mesoeconomics of abortion in the Middle East and North Africa. Methodologically, review papers are the most frequent study type, indicating that researchers rely on evidence from a core set of costing papers. Studies generating new primary data on mesoeconomic outcomes are needed to strengthen the evidence base.